Isu Gender, Disabilitas, dan Inklusi Sosial dalam Pendidikan Islam: Sebuah Tinjauan Kritis dan Strategis - Zeni Murtafiati Mizani (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
Issues of gender, disability, and social inclusion are important dimensions in the development of equitable, sustainable, and rights-based education. In the context of Islamic education in Indonesia, these three issues have not been fully integrated into systemic policies, curricula, and institutional practices. This article aims to map structural-social challenges as well as offer transformative strategies based on theological, sociological, and public policy approaches to realize inclusive Islamic education. Through a critical literature review of national policies such as the GEDSI KOMPAK and SKALA Strategies, as well as an intersectional approach in gender and disability analysis, it was found that Islamic education still faces various obstacles such as social stigma, curative approaches to disability, and patriarchal bias in religious interpretation. This article offers transformative strategies, including: reformulation of the maqāṣid al-shari'ah-based curriculum, inclusion training for educators, institutional affirmation in the 3T area, and integration of GEDSI-based disaggregated data. The concept of Islam as a religion of rahmatan lil 'alamin is a solid theological basis in order to form an Islamic education system that is just, humane, and responsive to the diversity of student needs.